Bacterial cyclomodulins: types and roles in carcinogenesis. (2nd January 2022) - Morgan, Radwa N.; Saleh, Sarra E.; Farrag, Hala A.; Aboulwafa, Mohammad M.
Abstract: Various studies confirmed that bacterial infections contribute to carcinogenesis through the excessive accumulation of reactive oxygen species (ROS) and the expression of toxins that disrupt the cell cycle phases, cellular regulatory mechanisms and stimulate the production of tumorigenic inflammatory mediators. These toxins mimic carcinogens which act upon key cellular targets and result in mutations and genotoxicities. The cyclomodulins are bacterial toxins that incur cell cycle modulating effects rendering the expressing bacterial species of high carcinogenic potentiality. They are either cellular proliferating or cell cycle arrest cyclomodulins. Notably, cyclomodulins expressing bacterial species have been linked to different human carcinomas. For instance, Escherichia coli species producing the colibactin were highly prevalent among colorectal carcinoma patients, CagA + Helicobacter pylori species were associated with MALT lymphomas and gastric carcinomas and Salmonella species producing CdtB were linked to hepatobiliary carcinomas. These species stimulated the overgrowth of pre-existing carcinomas and induced hyperplasia in in vivo animal models suggesting a role for the cyclomodulins in carcinogenesis. Wherefore, the prevalence and mode of action of these toxins were the focus of many researchers and studies. This review discusses different types of bacterial cyclomodulins highlighting their mode of action and possible role in carcinogenesis.